Der inkriminierte Bischof Könige im Konflikt mit Kirchenleitern im westgotischen und fränkischen Gallien (466-614) - Stüber, Till (Millennium-Studien / Millennium Studies, 2019)
In this study, Till Stüber analyzes loyalty conflicts between bishops and kings in post-Roman Gaul. He examines the political or social factors that resulted in these conflicts, and also explores the solutions that were found to avoid them. His approach offers fresh insights into the relationship between kings and bishops in this period.